Cytokine networks and therapeutic advances in systemic lupus erythematosus - Chen, Zeping; Liu, Shupei; Xie, Rui; Zhang, Pan; Feng, Yue (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the loss of immune tolerance, leading to the production of autoantibodies and widespread organ damage. Th1, Th2, and Th17 cytokines play critical roles in driving inflammation and tissue injury in SLE. IL-17 and IL-23 have been identified as key mediators in disease progression, with ongoing clinical trials assessing the efficacy of their inhibitors. Additionally, cytokines like IL-10 and IL-22 exhibit dual roles, influencing both pathogenic and protective immune responses. While targeted therapies have shown clinical promise, challenges related to safety and long-term efficacy persist. Emerging targets such as MIF and IL-39 offer new insights into disease mechanisms. This review summarizes the immunoregulatory functions of these cytokines, focusing on their contributions to disease pathogenesis and potential therapeutic strategies, highlighting the importance of cytokine in SLE treatments.